Death as a Cleansing of the Soul in the Work of Sarah Kane - Sadowski, Michał (Wzniosłość i makabra w literackich obrazach śmierci, 2014)
The article draws attention to the reversal dominant that is the death in works of Sarah Kane. Thescandalous writer presented a different kind of love and death. As a representative of „the Cool Britannia”in her plays engulfs the reader with the cruelty that is clean heroes and cause to the people woke upreal humanity. Is due to torture, disease, and death can save the world and its inhabitants? The writeras eloquent and innovative attempts to answer this question because of its small, but rich in creativity,prematurely terminated.